Humanistic thought and education for sustainable development - Kohl, Katrin; Sanusi, Zainal Abidin; Hussien, Suhailah (Oslo Metropolitan University University Library, 2024)
Education for Sustainable Development (ESD)is an educationconcept, central towhat is globally understood as quality educationandendorsed by the United Nations as a key enablerof all Sustainable Development Goals(SDGs). ESDhas been around for more than three decadesandhas sparked its ownacademic discourseand field of research. Yet, ESDis not fully embedded in all education systems and within societies. Although stakeholders from academia and practice are engaged in addressing ESDsinceitsinclusion in Agenda 21in 1992,there has been a struggle to develop a shared conceptual understanding. The discussion in theory and practice isstill underway, with researchers grappling in depth withthe understanding ofESD, its thematic width, concrete implementation,and tangible outcomes. Following the current quest by UNESCOto reconsider existing ways of knowing and to question where knowledge comes from and how we add to it,theauthorsof this articleexamined a sample ofESDliteratureonwhetherepistemic foundations of ESD including its role as a programwithin UNESCOare consideredin thediscourse. They concentrate in their review on humanist approachesas an important perspective for UNESCO.The resultspoint to a gap in thecurrentliterature. The authors also show that, if ESDwas grounded inhumanistic thought, itcouldpose abarrier for certainworldviewsto engage with or implement ESD. Therefore, ESD’s foundations requirefurther examination. This paper is a first step in drawing attention to the need to makeESD’s foundationsmore explicit.